2017
DOI: 10.4172/2155-9899.1000499
|View full text |Cite
|
Sign up to set email alerts
|

Gluten, Transglutaminase, Celiac Disease and IgA Nephropathy

Abstract: Both, celiac disease and IgA nephropathy are autoimmune diseases that are IgA mediated and share multiple clinical, pathophysiological, genetic, nutritional and immunological aspects. In view of recent observations and wider understanding of the central role played by the intestinal ecosystem in celiac disease and IgA nephropathy development, the present review highlights those shared aspects, concentrating on potential nutritional therapeutic strategies in IgA nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Celiac disease, dermatitis herpetiformis and celiac ataxia are induced by gluten-containing food products [ 1 , 2 , 3 ]. Many other autoimmune diseases might benefit from a gluten-free diet [ 5 , 14 , 15 , 16 ] or other restrictive dietary regimens [ 17 ]. Even an autoimmune neurological disease like polyradiculoneuropathy has been induced by porcine brains, although in this case the exposure of the affected abattoir workers was through aerosolized antigens and not per oral intake [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Celiac disease, dermatitis herpetiformis and celiac ataxia are induced by gluten-containing food products [ 1 , 2 , 3 ]. Many other autoimmune diseases might benefit from a gluten-free diet [ 5 , 14 , 15 , 16 ] or other restrictive dietary regimens [ 17 ]. Even an autoimmune neurological disease like polyradiculoneuropathy has been induced by porcine brains, although in this case the exposure of the affected abattoir workers was through aerosolized antigens and not per oral intake [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that the overexpression of tTG may lead to the retrotranscythosis of IgAbearing gliadin with increase IgA deposits. FcαRI/CD89 is probably involved in this mechanism by the direct interaction with gliadin and participation in the formation of IgA-sCD89 complexes [50]. Our previous studies [28,29] revealed the correlation between the intensity of CD89 cutaneous expression and anti-npG IgA detected with ELISA in DH, indicating that there is a single, shared pathway of DH-type IgA-mediated immune response to npG, tTG, and eTG.…”
Section: Discussionmentioning
confidence: 90%
“…IgA nephropathy (IgAN) is the most common primary glomerulonephritis [1], and deteriorates to uraemia in up to 40% of patients within ~20 years [2,3]. Recent studies have further characterised IgAN as an autoimmune disease with a multi‐hit pathogenetic process [4–6]. Clinically, although immunosuppressive drugs have been used to treat some IgAN patients, their efficacy in preserving renal function and reducing proteinuria in IgAN is insufficient and remains controversial.…”
Section: Introductionmentioning
confidence: 99%